The Effect of Chloro Acetic Acid Concentration and Temperature Reaction of Carboxymethyl Chitosan Formation on Cation Exchange Capacity and Thermal Stability - Purnawan, Candra; Pramono, Edi; Purwanto, Purwanto (ALCHEMY Jurnal Penelitian Kimia, 2014)
The research on the effect of chloro acetic concentration and temperature reaction of carboxymethyl chitosan formation on cation exchange capacity and thermal stability of polymer have been done. Carboxymethyl chitosan was synthesized by reaction of chitosan and chloro acetic acid with NaOH as catalyst. Polymer was characterized by Fourier Transform Infrared Spectrofotometer, cation exchange capacity test, and thermal analysis with thermogravimetric method. Carboxymethyl chitosan has strong FTIR adsorption of carboxyl group (-COO-) in 1606,70 cm-1 and 1444,68 cm-1. The increasing of chloro acetic acid concentration and reaction temperature decreased cation exchage capacity and changed thermal stability of polymer.